Thermogenic effect and substrate oxidation of protein from animal and plant sources in adults - Ahmed Fahmy Arif Tsani; Lee Myung Joo; Kim Eun Kyung (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2015)
Background: Changing nutrient source is one of the efforts to increase thermogenic effect (TEF) which may be significant for body weight reduction.Objective: The aim of this study was to investigate the effects of high protein diets using animal (chicken) and plant (tofu) sources on the thermogenic effect (TEF) and substrate oxidation.Method: Ten female adults (mean age 20.8+1.2 y) participated in two isocaloric diet ingestions. Each meal provided 30% of the daily basal energy need (32/26/42% as protein/fat/carbohydrates, respectively). Postprandial energy expenditure was measured by indirect calorimetry.Results: There were no significant differences in TEF and substrate oxidation. The postprandial fat oxidation rate was higher than that at the preprandial state, while carbohydrate and protein oxidation rates were lower.Conclusion: No differences were observed in TEF and substrate oxidation in animal- and plant-based diets. A high protein diet could be beneficial for weight loss, but animal protein does not appear to offer superior benefits compared to plant protein.